Process Modeling of an Advanced NH3 Abatement and Recycling Technology in the Ammonia-Based CO2 Capture Process - Li, K.; Yu, H.; Tade, Moses; Feron, P.; Yu, J.; Wang, S. (American Chemical Society, 2014)
An advanced NH3 abatement and recycling process that makes great use of the waste heat in flue gas was proposed to solve the problems of ammonia slip, NH3 makeup, and flue gas cooling in the ammonia-based CO2 capture process. The rigorous rate-based model, RateFrac in Aspen Plus, was thermodynamically and kinetically validated by experimental data from open literature and CSIRO pilot trials at Munmorah Power Station, Australia, respectively. After a thorough sensitivity analysis and process improvement, the NH3 recycling efficiency reached as high as 99.87%, and the NH3 exhaust concentration was only 15.4 ppmv. Most importantly, the energy consumption of the NH3 abatement and recycling system was only 59.34 kJ/kg CO2 of electricity. The evaluation of mass balance and temperature steady shows that this NH3 recovery process was technically effective and feasible. This process therefore is a promising prospect toward industrial application.